2014
DOI: 10.1007/s00726-014-1859-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 99mTc-ZIGF1R:4551-GGGC affibody molecule, a new probe for imaging of insulin-like growth factor type 1 receptor expression

Abstract: Overexpression of insulin-like growth factor-1 receptor (IGF-1R) in several cancers is associated with resistance to therapy. Radionuclide molecular imaging of IGF-1R expression in tumors may help in selecting the patients that will potentially respond to IGF-1R-targeted therapy. Affibody molecules are small (7 kDa) non-immunoglobulin-based scaffold proteins that are well-suited probes for radionuclide imaging. The aim of this study was the evaluation of an anti-IGF-1R affibody molecule labeled with technetium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 46 publications
3
20
1
Order By: Relevance
“…This indicated that the main reason of the release was re-oxidation of technetium. This was not what we have observed earlier for anti-HER2 and anti-IGF-1R affibody molecules, where even -GGGC provided a stable attachment of 99m Tc and 188 Re (Wållberg et al 2011; Altai et al 2012, 2014a, b; Mitran et al 2015). A possible explanation for the current results is that some side chains in the affibody molecules form an alternative chelating pocket and a part of technetium is bound not only to a cysteine-containing chelator, but also to this much weaker site.…”
Section: Discussioncontrasting
confidence: 66%
“…This indicated that the main reason of the release was re-oxidation of technetium. This was not what we have observed earlier for anti-HER2 and anti-IGF-1R affibody molecules, where even -GGGC provided a stable attachment of 99m Tc and 188 Re (Wållberg et al 2011; Altai et al 2012, 2014a, b; Mitran et al 2015). A possible explanation for the current results is that some side chains in the affibody molecules form an alternative chelating pocket and a part of technetium is bound not only to a cysteine-containing chelator, but also to this much weaker site.…”
Section: Discussioncontrasting
confidence: 66%
“…Because of their small size, affibody can be synthesized or recombinantly expressed. Since the first construct HER2-targeting affibody molecule Z HER2:342 was produced and confirmed to bind to HER2-positive cancer cell lines [24], several similar affibody molecules targeting EGFR [23,24], HER3 [27,28], IGF-1R [42], HIV-1-gp120 [43] and HPV16E7 [30,31] have been reported and also applied to image several tumour-associated molecular targets, such as HER2 [25,44], EGFR [45,46], HER3 [47]. The first clinical imaging study on patients with breast cancer was conducted using HER2-specific affibody, which Mice bearing C666-1tumor grafts were intravenously injected with 100 nmol/kg Z142X, Z142, or an equal amount of control agents or the same volume of PBS every two days for 15 times via tail vein.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, preclinical studies demonstrated feasibility of application of affibody molecules for imaging several molecular targets in cancer xenografts, e.g. EGFR (33), HER3 (48) IGF-1R (49), PDGFRβ (50) and CAIX (51). It would be attractive to apply our experience in development of HER2-imaging affibody molecule probes for development of probes to new targets.…”
Section: Discussionmentioning
confidence: 99%